Investigation on the Learning Programming Techniques via Mobile Learning Application - Amro, Jamal Salem; Romli, Rohaida (2019 4th International Conference and Workshops on Recent Advances and Innovations in Engineering (ICRAIE), 2019)
In resolving the difficulties of learning certain concepts of programming, various teaching and learning programming techniques have been proposed such as Trace- Driven, Problem Solving, Game-based, and Visualization particularly help to develop creative thinking and enhance students' engagement in learning. With the availability of mobile devices technology, numerous m-learning applications for learning programming available via Google Play and Apple Stores as well as those developed from research works. However, it is very hard to find any published evidence that reveal empirical results pertaining to the usage of m-learning apps as one of the most efficient techniques of learning programming. Hence, this study aims to investigate the extent of the available m-learning applications via Google Play and Apple Stores in utilizing various programming techniques to support effective learning of programming. A controlled experiment was conducted on three (3) selected m-learning applications namely Sololearn, Programming Hub, and Mimo. The results reveal that Mimo, which utilizes the Trace-Driven, Visualization and Problem Solving techniques, is the most preferred application. The utilization of this application in programming classes is recommended as it could serve as an alternative learning medium to improve learners' ability in understanding basic programming concepts efficiently. Besides, this application can be used as a benchmark of the best-utilized learning programming techniques on the future design of related m- learning applications.